Do probiotics prevent antibiotic-associated diarrhoea? Results of a multicentre randomized placebo-controlled trial. Issue 2 (June 2020) - Rajkumar, C.; Wilks, M.; Islam, J.; Ali, K.; Raftery, J.; Davies, K.A.; Timeyin, J.; Cheek, E.; Cohen, J.; ,
Summary: Background: Antibiotic-associated diarrhoea (AAD) is a side-effect of antibiotic consumption and probiotics have been shown to reduce AAD. Methods: A multicentre, double-blind, placebo-controlled, randomized trial was conducted to evaluate the role of Lactobacillus casei DN114001 (combined as a drink with two regular yoghurt bacterial strains) in reducing AAD and Clostridioides difficile infection in patients aged over 55 years. The primary outcome was the incidence of AAD during 2 weeks of follow-up. Results: A total of 1127 patients (mean age ± standard deviation: 73.6 ± 10.5) were randomized to the active group ( N = 549) or placebo group ( N = 577). Both groups were followed up as per protocol. The proportion of patients experiencing AAD during follow-up was 19.3% (106/549) in the probiotic group vs 17.9% (103/577) in the placebo group (unadjusted odds ratio 1.10, 95% confidence interval 0.82–1.49, P = 0.53). Conclusions: No significant evidence was found of a beneficial effect of the specific probiotic formulation in preventing AAD in this elderly population drawn from a number of different UK hospitals. However, in the UK and in many other healthcare systems there have, in recent years, been many changes in antibiotic stewardship policies, an overall decrease in incidence in C. difficile infection, as well as an increased awareness of infection prevention, and modifications in nursing practice. In light of these factors, it is impossible to conclude definitively from the current trial that the study-specific probiotic formulation has no role in preventing AAD, and it is our view that further trials may be indicated, controlling for these variables.